2020
DOI: 10.3233/blc-200277
|View full text |Cite
|
Sign up to set email alerts
|

The Urinary Microbiome and Bladder Cancer: Susceptibility and Immune Responsiveness

Abstract: Bladder cancer is a highly prevalent disease worldwide and is associated with a high mortality rate. Across all stages of bladder cancer, immunotherapy has now become the cornerstone of treatment. The commensal microbiome has become a major focus of research given its impact on numerous states of human health and disease. Many links between commensal microbes and immune function have been reported. Recently a commensal urinary microbiome has been identified and characterized in healthy individuals by several r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
0
22
0
3
Order By: Relevance
“…The urinary microbiome has since been implicated in UBC [16]. Studies found differences in microbe abundance between urine of healthy patients and UBC patients; however, the mechanisms of how different microbe abundances may interact with EMT and ECM-related protein expression remains unclear [16]. In this study, we correlated the abundance of intra-tumor bacteria to the expression of genes involved in MIBC EMT, including genes encoding for ECM proteins.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The urinary microbiome has since been implicated in UBC [16]. Studies found differences in microbe abundance between urine of healthy patients and UBC patients; however, the mechanisms of how different microbe abundances may interact with EMT and ECM-related protein expression remains unclear [16]. In this study, we correlated the abundance of intra-tumor bacteria to the expression of genes involved in MIBC EMT, including genes encoding for ECM proteins.…”
Section: Introductionmentioning
confidence: 96%
“…For decades, the urinary tract and urine were believed to be sterile. However, recent studies challenged this idea, and it is now widely accepted that the urinary tract, including the bladder, is not sterile [16]. The urinary microbiome has since been implicated in UBC [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing number of studies investigating the microbiome in benign urological conditions,15–20 but only a few studies to date have explored the role of the urinary microbiome in urological malignancies 21–25. Xu et al showed that Streptococcus abundance was significantly elevated in urine specimen from urothelial carcinoma patients compared with healthy individuals 21.…”
Section: Introductionmentioning
confidence: 99%
“…Especially important is gut microbiota, whose disruption can lead to cancer generation by promotion of chronic inflammation, alteration of normal metabolism, genotoxicity, and weakening of the immune response ( 4 ). The microbiome is also present in the urinary tract, which for a long time was considered sterile ( 6 ). Recent studies have shown that modulation of the microbiome can improve therapeutic response to immune checkpoint inhibitors, which can influence the effectiveness of immunotherapy in cancer treatment ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%